Mechanism by which ammonium bicarbonate and ammonium sulfate inhibit mycotoxigenic fungi. - DePasquale, D A (1990)
In this study we examined the mechanism by which ammonium bicarbonate inhibits mycotoxigenic fungi. Elevated extracellular pH, alone, was not responsible for the antifungal activity. Although conidia of Penicillium griseofulvum and Fusarium graminearum had internal pH (pHi) values as high as 8.0 in buffer at an external pH (pHo) of 9.5, their viability was not markedly affected. The pHi values from conidia equilibrated in glycine-NaOH-buffered treatments without ammonium bicarbonate or ammonium sulfate were similar to values obtained from buffered treatments containing the ammonium salts. Thus, inhibition did not appear to be directly related to increased pHi. Ammonium sulfate in buffered media at pH greater than or equal to 8.7 was as inhibitory as ammonium bicarbonate, but was completely ineffective at pH less than or equal to 7.8. The hypothesis that free ammonia caused the fungal inhibition was tested by using ammonium sulfate as a model for ammonium bicarbonate. Viability, expressed as log CFU/ml, and percent germination of P. griseofulvum and F. graminearum decreased dramatically as the free ammonia concentration increased. Germination rate ratios (the germination rate in buffered ammonium sulfate divided by the germination rate in buffer alone) decreased linearly as the free ammonia concentration increased, further establishing NH3 as the toxic agent. Ammonium bicarbonate inhibits fungi because the bicarbonate anion supplies the alkalinity necessary to establish an antifungal concentration of free ammonia.